Enviromental impact assessment of cement industry using Leopold Matrix - Sabah Alwan , Wafaa; Khaleefah ALrikabi , Nada (Journal of Planner and Development, 2022)
The assessment of the environmental impact of the cement industry using the Leopold Matrix is ​​to determine the negative and positive impacts on the environment resulting from this industry, and what are the long-term and short-term effects, direct and indirect, and the amount of these effects and potential risks, and that this evaluation process is done through a number of methods, including Matrix method, including (Leopold).  The importance of the research because the cement occupies is of great importance in the world, especially in our country, Iraq, in the sector of construction and modernity, and the toxic emissions and solid waste produced by the production of this material.   Environmental problems resulting from this industry have been addressed. The basic problem of the cement industry is determined in the environmental field because of the cumulative effect it has on the environment and production capacity on the surrounding environment.  The main objective of conducting the research is to assess the environmental impacts of major industrial projects, especially cement, one of the analytical methods in urban planning, which can contribute to reducing the negative effects on the environment and on the uses of the surrounding land. Among the disadvantages of this industry is that it       increases air, soil and water pollution, as well as leveling the lands and decreases the health safety of workers through the emissions they cause,   perhaps the most prominent of which are carbon dioxide (CO2), carbon dioxide (CO), and methane (CH4).   As these gases lead to direct air pollution, especially in the areas surrounding the plant.The Kirkuk cement plant is one of the major economic development projects in the country as it provides a national and local product to support other construction projects, and at the same time it is a category A polluting industry and therefore it is necessary to sign it outside the cities, and it requires an environmental impact assessment prepared in advance according to a detailed study that includes problems and impacts. Expected and solutions to it.  The evaluation process is to ensure the protection, improvement and preservation of the environment and natural resources. Therefore, the research considers the necessity to oblige the owners of cement projects to implement the environmental requirements mentioned in the environmental legislation brochure in force, and to develop a strategy to mitigate the negative impacts and alternative options in the production process.